Versatile system for ion energy measurements generated by pulsed laser ionization: Insights into electron-ion dynamics - Serpa, Rafael Bento; Aloui, Tanouir; Ross, Daniel; Keogh, Justin; Parker, Charles B.; Denton, M. Bonner; Glass, Jeffrey T.; Amsden, Jason J. (Spectrochimica acta. Part B: Atomic spectroscopy, 2025)
Ion energy distributions generated by pulsed laser interactions with materials are essential for applications ranging from materials science to oncology. Ion energy characterization is particularly important for an emerging mass spectrometry technique called virtual-slit cycloidal mass spectrometry (VS-CMS). The ion energy distribution influences the design and performance of VS-CMS instruments, as well as the efficacy of laser-driven ionization methods in various fields. Several established techniques, including the retarding potential method, time-of-flight (TOF) analysis, and electrostatic energy analyzers, have been employed to measure ion energy distributions. The wide range of ion energies reported highlights the strong dependence of ion energy on laser parameters, target materials, and experimental conditions, as well as the necessity of making independent measurements of the ion energy distribution for specific laser systems and materials. This paper presents the design and characterization of a simple TOF-based apparatus for measuring ion energy distributions from pulsed laser ionization without external fields. This approach minimizes perturbation of electron-ion dynamics and enables simultaneous energy measurements at multiple spatial positions. The apparatus was tested using a nanosecond pulsed Nd:YAG laser operating at 1064 nm, 532 nm, and 266 nm on solid copper sheets at various laser fluences. Simultaneous measurements at different distances provide new insights into ion-electron interactions post-ionization and demonstrate the influence of laser wavelength and fluence on ion energy distributions. [Display omitted] •Reliable and versatile system for ion energy measurement.•System for simultaneous ion energy measurement at different distances from ion source.•Contribution of electron-induced fields and laser fluence to the ion energy.